Integration by Sport Activities: Resource or Only a Paradox? - Giovanna Russo (Journal of Mediterranean Knowledge, 2019)
Nowadays in Europe sport and physical activity represent a strategic tool for public health policiesthat aim to promote the wellbeing of population, supporting dialogue for social cohesion and, at the same time, represent an important economic sector. The acknowledgement of sport capability to be a vehicle for integrating diversity- confirming the attention to intercultural dialogue at European level –in an evidence of its importance in the current debate on integration and multiculturalism. Through comparing different sports models of integration within the EU, this paper is going to discuss some questions: what connection is there between the construction of a multicultural society and the diffusion of sports practices? What meanings, values and paradoxes coexist today in the culture of integration implemented in Europe? Is the “sports” habitus a field of competition between migrants and natives, or a space of integration for generations of new citizens?